Last night at Chateau Marmont [compact disc, unabridged] - Weisberger, Lauren, 1977- (Simon and Schuster Audio, 2010)
Lauren Weisberger, author of The Devil Wears Prada, presents a new salacious tome about a couple of everyday girls plotting revenge against their celebrity ex-boyfriends.